A longitudinal analysis of MPOWER implementation, 2008-2018 - Les Hagen; Gholamreza Heydari; Fadi Hammal (Inishmore Laser Scientific Publishing Ltd, 2022)
# Background In 2008, the World Health Organization (WHO) introduced *MPOWER*-a package of evidence-based, high-impact policy measures to help countries reduce tobacco use. These measures align with selected articles within the World Health Organization's Framework Convention on Tobacco Control (FCTC), a global public health treaty to prevent and reduce tobacco use. # Methods Observational longitudinal study involving 195 countries that submitted biannual national reports between 2008 and 2018. To report changes in MPOWER scores, countries were assessed using a validated checklist of the seven MPOWER indicators and a maximum possible unweighted composite score of 34 points. Covariate analysis was conducted among selected health, sociopolitical, and economic indicators. # Results 176 out of 195 countries improved their MPOWER scores between 2008 and 2018, with two achieving full implementation (Brazil and Turkey). Twenty-three (23) countries representing 11.2% of the global population recorded an MPOWER scoring increase of at least 10 points between 2008 and 2018. The overall mean 10-year scoring increase was 5.1 points or a relative improvement of 27.1%. In 2018, 20 countries representing 10.4% of the global population excelled in MPOWER implementation by receiving a total composite score of at least 30 of 34 possible points. The MPOWER elements with the highest degree of implementation in 2018 include *Warn* (package), *Protect* (smoking ban) and *Enforce* (ad ban). Several covariates were positively associated with higher levels of MPOWER implementation, including *cigarette affordability,* the *existence of national tobacco control objectives,* the *human development index score*, the *national corruption index score, national literacy rates* and the *political regime index score.* # Conclusions MPOWER implementation increased markedly between 2008 and 2018 in all seven WHO regions and countries representing all four World Bank income classifications. However, only two countries achieved full implementation by 2018. More work is needed to improve MPOWER implementation. Countries with low-income levels, compromised human development, reduced literacy rates, higher rates of corruption, and autocratic political regimes appear to struggle more with MPOWER implementation.